Peranan aerasi dan silika serta lama pemeraman terhadap kandungan pupuk cair lumpur organik unit gas bio - Mochammad Junus; Agung Sugeng Widodo; Wahyono Suprapto; Windi Zamrudy (Faculty of Animal Science, Universitas Brawijaya, 2014)
Organic Sludge Biogas Unit (OSBGU) is a product that was generally less noticed by the owner. Filtering solids and liquids of OSBGU would be very helpful for feedstuffs and fertilizer plants. Giving aeration and silica in the fluid of OSBGU as long ripening treatment with 1, 2, 3, 4 and 7 days was expected to transform the liquid into a better liquid fertilizer of OSBGU. The results showed that the effect of treatment, fermentation time and the interaction among them on the content of liquid OSBGU manure on pH, organic C, N total, C/N ratio, and organic matter was highly significant (P<0.01), except for total N did not have differences (P>0.05). The study concluded that the role of aeration and the addition of silica and long ripening and their interaction was very influential on the content of liquid OSBGU manure on pH, organic C, C/N ratio and organic ingredients, except the N total. The study suggested to use aeration and if necessary by adding silica and fermentation time until on day 7 to improve the content of liquid OSBGU manure. Keywords: organic sludge biogas unit, pH, organic C, total N, C/N ratio, material organic, fermentation time